Winemaking with vine-shoots. Modulating the composition of wines by using their own resources. (July 2019) - Cebrián-Tarancón, Cristina; Sánchez-Gómez, Rosario; Cabrita, María João; García, Raquel; Zalacain, Amaya; Alonso, Gonzalo L.; Salinas, M. Rosario
Abstract: Vine-shoots from two important Vitis vinifera, Airén and Cencibel, have been prepared in two different formats ( chip and granule ) and added (12 g/L) in their own wines in different winemaking steps. Results have shown significant differences depending in all conditions tested, and wine chemical composition was modulated while in contact with vine-shoots. Compounds such as trans -resveratrol, increased its concentration up to 4 mg/L in Airén white wines. In Cencibel red wines, vanillin was found in a concentration four times above its odor threshold and independently of the vine-shoot variety, format and moment of addition, compounds such as (−)-epicatechin and (+)-catechin increased the concentration with respect to the control wine. When vine-shoots were added after fermentation, β-ionol appeared for first time in all wines. In case of guaiacol, the higher increment was observed for Airén wines. Therefore, it is possible to elaborate distinctive wines using their own resources. Graphical abstract: Unlabelled Image Highlights: Winemaking with vine-shoots as enological additive it is possible. Granule and chip formats were used in two steps of winemaking. Significant release of volatile compounds were quantified in wines, especially vanillin. An important increases of trans -resveratrol was quantified. Circular viticulture, a new concept to connect viticulture and enology